SMOKING OUT THE FACTS IN FLIGHT (Tufts Archival Research Center, 2007)
Article regarding the issue of air quality on airplanes. Presents the different arguments, that secondhand smoke is bad for you and that it has no measurable effect and discusses the valid points of each side. Concludes with an assessment that there has not been enough scientific evidence to prove that secondhand smoke is dangerous.